Association between human leucocyte antigen subtypes and risk of end stage renal disease in Taiwanese: a retrospective study. Issue 1 (December 2015) - Dai, Ciou-Sia; Chu, Chen-Chung; Chen, Shin-Fan; Sun, Chiao-Yin; Lin, Marie; Lee, Chin-Chan
Abstract Background End stage renal disease (ESRD) is prevalent in Taiwan. Human leukocyte antigens (HLA) have been found to be associated with the pathogenesis of autoimmune diseases, allergies and inflammatory bowel diseases, and there are emerging evidences of correlations between HLA genotypes and renal diseases such as diabetic nephropathy, IgA nephropathy, and glomerulonephritis. The aim of this study is to investigate detailed HLA subtypes in a case-control study of Taiwanese individuals. Methods The polymorphisms of HLA class I and II antigens in ESRD patients and a healthy control group were retrospectively analyzed. The information of 141 ESRD patients was obtained from the medical record of the Keelung branch of Chang Gung Memorial Hospital and was compared to the HLA type of a control group comprized of 190 healthy unrelated Taiwanese from one of our previous studies. In order to standardize the HLA designation of prior low-resolution typings with the more advanced DNA based typings, all HLA-A, −B and -DR were analyzed using a low resolution serologic equivalent. Results The current work suggests that HLA-DR3 (odds ratio = 1.91, 95 % CI = 1.098–3.324, P = 0.024, Pc = 0.312) and HLA-DR11 (odds ratio = 2.06, 95 % CI = 1.133–3.761, P = 0.021, P c = 0.273) may represent susceptibility risk factors for the development of ESRD in Taiwanese individuals. On the other hand, HLA-DR8 (odds ratio = 0.47, 95 % CI = 0.236–0.920, p = 0.027. Pc = 0.351) may be a protective factor. HLA-A and -B antigens did not show any contribution of progression to ESRD. However, we note that the significance of all these findings is lost when the results are corrected for multiple comparisons according to Bonferroni. Further investigation with a larger group of patients and control is needed to resolve this issue. Conclusions HLA typing might be a useful clinical method for screening patients with high risk of progression to ESRD.